Method for removing residual acid in photoresist resin
By using a mixed resin of cation exchange resin and anion exchange resin to treat the photoresist resin, the problem of deprotection reaction and low film retention caused by residual acid in the photoresist resin is solved, and efficient removal of acid and metal impurities is achieved, and process efficiency and product quality are improved.
Patent Information
- Application Number
- CN202311336412.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-18
AI Technical Summary
In the existing photoresist resin purification process, residual acid leads to a deprotection reaction, and the film retention rate is low after development. The traditional water rinsing method increases the process time and cost, and introduces water impurities.
A mixed resin, including a mixture of cation exchange resin and anion exchange resin, is prepared by heating curing, the resin ratio is adjusted to achieve optimal acid removal, and a pre-exchange treatment is performed before use to remove moisture.
Effectively remove residual acid in the photoresist resin, avoid deprotection reactions, increase the film retention rate by no less than 85%, and at the same time remove metal impurities and moisture, reducing process time and cost.
Smart Images

Figure CN119846900A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor integrated circuits, in particular to resin purification technology, and specifically relates to a method for removing residual acid in photoresist resin. Background Art
[0002] Photoresist resin is an important component of photoresist. In order to meet the performance requirements of photoresist, the metal impurities and moisture of photoresist resin must be processed to a relatively low level. In the traditional industrial photoresist resin purification process, the photoresist resin system will be acidic after purification. If the photoresist resin purified by the traditional purification method is not subjected to post-treatment to remove the acid, the photoresist resin will undergo a deprotection reaction, and the film retention rate after development is extremely low, which obviously does not meet the requirements of photoresist. In order to solve the problem of acid residue and low film retention rate in photoresist resin, the common practice is to use a method of water rinsing photoresist resin. Although water rinsing can remove the acid in the photoresist resin to a certain extent, it will cause an increase in process time and cost, and will also introduce water impurities. Therefore, it is of great practical significance to study and develop a simple method for removing residual acid in photoresist and keeping the moisture of photoresist resin at an extremely low content level at the same time. Summary of the invention
[0003] In order to solve the problems of high residual acid content and low film retention rate in existing photoresist resins, the present invention provides a method for removing residual acid in photoresist resins. The method can well achieve the removal of residual acid in photoresist resins, can avoid the occurrence of photoresist resin deprotection reaction caused by residual acid, and the film retention rate of the treated photoresist resin is not less than 85%. The method can also further remove metal impurities and moisture in the photoresist resin.
[0004] The technical solution adopted by the present invention is as follows:
[0005] A method for removing residual acid in a photoresist resin comprises: purifying the photoresist resin to be treated by using a mixed resin, wherein the mixed resin is a resin formed by mixing a cation exchange resin and an anion exchange resin.
[0006] According to an embodiment of the present invention, the photoresist resin is KrF photoresist resin.
[0007] According to an embodiment of the present invention, the photoresist resin to be treated contains an acid. Specifically, the acid is an organic acid and / or an inorganic acid, and illustratively the acid includes but is not limited to at least one of sulfonic acid, nitric acid and hydrochloric acid.
[0008] According to an embodiment of the present invention, the total acid content in the photoresist resin to be treated is not less than 50 mg KOH / g, for example, not less than 60 mg KOH / g.
[0009] According to an embodiment of the present invention, the photoresist resin to be treated contains metal impurities. Exemplarily, the metal impurities include but are not limited to at least one of Li, Na, Mg, Al, K, Ca, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Pd, Ag, Cd, Sn, Au and Pb.
[0010] According to an embodiment of the present invention, the total content of metal impurities in the photoresist resin to be treated is not less than 10 ppm, such as not less than 50 ppm, and for example not less than 100 ppm.
[0011] According to an embodiment of the present invention, the photoresist resin to be treated contains moisture.
[0012] According to an embodiment of the present invention, the moisture content in the to-be-treated photoresist resin is not less than 2%, such as not less than 5%, and for example not less than 8%.
[0013] According to an embodiment of the present invention, the system in which the photoresist resin to be treated exists is a system in which an organic solvent exists, that is, the photoresist resin to be treated exists in a form mixed with an organic solvent. Exemplarily, the organic solvent is at least one of an ester organic solvent, an alcohol organic solvent, and an ether organic solvent.
[0014] According to an embodiment of the present invention, the ester organic solvent, alcohol organic solvent and ether organic solvent are commonly used in the field of photoresist resin, especially in the field of KrF photoresist resin.
[0015] Exemplarily, the ester organic solvent is propylene glycol methyl ether acetate (PGMEA); and the alcohol organic solvent is methanol.
[0016] According to an embodiment of the present invention, the cation exchange resin is, for example, a strong acid cation exchange resin. Specifically, the cation exchange resin is selected from styrene sulfonic acid resin; more specifically, the comonomers of the cation exchange resin are styrene and divinylbenzene, the matrix is gel, and the functional group is a sulfonic acid group; illustratively, the cation exchange resin is a strong acid 1200Na cation exchange resin (the copolymer of the resin is a styrene-divinylbenzene copolymer, the matrix is gel, and the functional group is a sulfonic acid group).
[0017] According to an embodiment of the present invention, the anion exchange resin is, for example, a strong base anion exchange resin. Specifically, the anion exchange resin is selected from a styrene-based aminated resin; more specifically, the comonomers of the anion exchange resin are styrene and divinylbenzene, and the functional group is -N(CH3)3-; illustratively, the anion exchange resin is a strong base 4200Cl anion exchange resin (the copolymer of the resin is a styrene-divinylbenzene copolymer, and the functional group is -N(CH3)3-).
[0018] According to an embodiment of the present invention, the mass ratio of the cation exchange resin to the anion exchange resin in the mixed resin is 1:1.5 to 4, for example, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5 or 1:4. By adjusting the mass ratio of the cation exchange resin to the anion exchange resin, the optimal acid removal effect can be obtained, and the adsorption capacity for metal impurities can also be adjusted.
[0019] According to an embodiment of the present invention, the mixed resin is prepared by the following method:
[0020] The mixed resin is prepared by mixing Lewis acid, cation exchange resin and anion exchange resin, and heating and curing.
[0021] Wherein, the Lewis acid is selected from aluminum chloride and / or ferric chloride.
[0022] Wherein, the mass ratio of the cation exchange resin to the anion exchange resin is 1:1.5-4, for example, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5 or 1:4.
[0023] The mass of the Lewis acid accounts for 1-5wt% of the total mass of the cation exchange resin and the anion exchange resin, such as 1wt%, 2wt%, 3wt%, 4wt% or 5wt%.
[0024] The heating curing temperature is 100-150°C, for example, 100°C, 120°C, 130°C, 140°C or 150°C; the heating curing time is 2-8 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours.
[0025] According to the embodiment of the present invention, the mixed resin after heating and curing can fully exert its ability to remove acid in the photoresist resin and adsorb metal impurities, thereby improving the efficiency of removing acid from the photoresist resin and purifying metal impurities.
[0026] According to an embodiment of the present invention, the mixed resin is pre-exchanged with an alcohol organic solvent (such as methanol, ethanol, etc.; preferably methanol) before use, with the aim of further removing moisture in the mixed resin and that which may be produced during the ion exchange reaction between the mixed resin and the photoresist resin, thereby improving the purification effect of the photoresist resin.
[0027] According to an embodiment of the present invention, the mixed resin is loaded into a chromatography column to form a photoresist resin purification unit.
[0028] According to an embodiment of the present invention, the purification unit includes a plurality of chromatography columns. The number of chromatography columns in the purification unit can be reasonably adjusted according to the amount of the photoresist resin to be processed to ensure the acid removal effect on the photoresist resin and the removal efficiency of metal impurities.
[0029] Exemplarily, the purification unit is formed by four chromatography columns (such as PFA columns) connected in series via pipelines (such as PFA hoses), and the chromatography columns are filled with mixed resins.
[0030] The inner diameter of the chromatography column is not particularly defined, for example, 5 to 50 cm, such as 5 cm, 10 cm, 15 cm, 20 cm, 25 cm, 30 cm, 35 cm, 40 cm, 45 cm or 50 cm.
[0031] According to an embodiment of the present invention, at room temperature and pressure, the photoresist resin to be treated passes through a purification unit, ie, a chromatography column filled with mixed resin, at a flow rate of 2 to 50 ml / min.
[0032] According to an embodiment of the present invention, the method has better acid removal performance for photoresist resin, and can also process metal impurities and moisture in the photoresist resin, with good purification effect, and can obtain photoresist resin powder or clear and transparent photoresist resin glue as needed.
[0033] Specifically, a photoresist resin containing metal impurities and acid is passed through a mixed resin, wherein the mixed resin is obtained by mixing cation exchange resin and anion exchange resin in different proportions and curing by heating, and the mixed resin is pre-exchanged with an alcohol organic solvent before use; when the photoresist resin is contacted with such a mixed resin, the metal impurities in the photoresist resin can replace hydroxide ions after the anion exchange resin in the mixed resin contacts the photoresist resin, and the metal impurities in the photoresist resin can replace hydrogen ions after the cation exchange resin contacts the photoresist resin; the replaced hydrogen ions and hydroxide ions will undergo a neutralization reaction, and in this way, the removal of metal impurities in the photoresist resin is well achieved, and since the mixed resin is treated with an alcohol organic solvent, new moisture will not be introduced. At the same time, since the metal impurities and moisture in the photoresist resin have a small volume, they can also be freely adsorbed into the microscopic pores of the mixed resin, thereby achieving the purpose of further removing metal impurities and moisture in the photoresist resin. Moreover, since the content of anion exchange resin in the mixed resin is higher, more hydroxide ions can be replaced when in contact with the photoresist resin, which can give full play to the acid removal performance of the mixed resin and achieve the best acid removal effect. More importantly, since the cation exchange reaction and the anion exchange reaction can occur at the same time, the hydroxide ions exchanged by the anion exchange resin and the hydrogen ions exchanged by the cation exchange resin will immediately undergo a neutralization reaction, and hydrogen ions or hydroxide ions will not accumulate, thereby avoiding the occurrence of deprotection reactions caused by residual acid. The photoresist resin treated with the mixed resin can still retain a high film retention rate after development.
[0034] According to an embodiment of the present invention, the method further comprises filtering, that is, filtering the photoresist resin after the mixed resin purification process.
[0035] Specifically, the photoresist resin processed by the purification unit is sent to a filter for filtration.
[0036] According to an embodiment of the present invention, the purpose of the filtration is to remove particles in the photoresist resin system. The particles are, for example, particles produced by introducing solid components such as mixed resin into the photoresist resin system after being processed by a purification unit, or particles existing in the photoresist resin solution.
[0037] According to an embodiment of the present invention, the method further comprises: using a precipitant n-heptane to precipitate the purified photoresist resin, then collecting the solid photoresist resin after filtering, and then removing the precipitant n-heptane through vacuum drying to obtain photoresist resin powder.
[0038] According to an embodiment of the present invention, the content of total metal impurities in the photoresist resin (specifically, photoresist resin powder) is less than or equal to 1000ppb, such as less than or equal to 800ppb, such as less than or equal to 600ppb, such as less than or equal to 500ppb, such as less than or equal to 300ppb, such as less than or equal to 100ppb. The moisture content in the photoresist resin (specifically, photoresist resin powder) is less than or equal to 0.5%, such as less than or equal to 0.4%, such as less than or equal to 0.3%, such as less than or equal to 0.2%, such as less than or equal to 0.1%, such as less than or equal to 0.08%.
[0039] According to an embodiment of the present invention, the film retention rate of the photoresist resin glue is not less than 85%, preferably not less than 90%. The photoresist resin glue is a photoresist resin glue containing 30% PGMEA formed by dissolving purified photoresist resin powder in a PGMEA organic solvent, and the film retention rate of the photoresist resin glue containing 30% PGMEA after pre-baking, developing and post-baking is not less than 85%, preferably not less than 90%.
[0040] The beneficial effects of the present invention are:
[0041] The present invention uses a mixed resin to remove residual acid in a photoresist resin, and has the advantages of simple method, good effect, low cost and large preparation amount. At the same time, the content of metal impurities and water in the photoresist resin treated with the mixed resin (especially a strong acid and strong base type mixed bed ion exchange resin) is extremely low, and the acid in the photoresist resin can be removed while avoiding the occurrence of a photoresist resin deprotection reaction caused by the residual acid.
[0042] The method of the present invention solves the problems of residual acid and low film retention rate in the purification process of photoresist resin well, and avoids the occurrence of deprotection reaction caused by residual acid of photoresist resin. The method is simple and easy to operate, and greatly reduces the process time and cost of processing photoresist resin. Specifically, the method of the present invention can effectively remove the acid in the photoresist resin, and the method has the advantages of short process time, low cost. In addition, the removal rate of metal impurities in the photoresist resin reaches 99.99%, and the water content in the photoresist resin is not higher than 0.5%. After the mixed resin removes the metal impurities and moisture in the photoresist resin, the obtained photoresist resin has a film retention rate of more than 85% (preferably more than 90%) after the glue is prepared and developed. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a comparison chart of the NMR characterization of the photoresist resin before and after purification of Example 1.
[0044] Figure 2 This is a comparison chart of the nuclear magnetic resonance characterization of the purified photoresist resins of Example 1 and Example 4.
[0045] Figure 3 This is a comparison chart of the NMR characterization of the photoresist resin before and after purification of Comparative Example 1.
[0046] Figure 4 Schematic diagram of the process flow for treating residual acid in photoresist resin for mixed resin. DETAILED DESCRIPTION
[0047] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0048] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0049] The metal impurities in the photoresist resin to be treated used in the following embodiments include, but are not limited to, Li, Na, Mg, Al, K, Ca, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Pd, Ag, Cd, Sn, Au and Pb, and the total content of the metal impurities is 100 ppm.
[0050] The moisture content of the photoresist resin to be treated used in the following examples is 8%.
[0051] In the following examples, the metal impurities and water content in the purified photoresist resin were tested by ICP-MS and Karl Fischer test, respectively.
[0052] The photoresist resin paste in the following examples is prepared by the following method: dissolving the obtained photoresist resin powder in a PGMEA organic solvent to form a photoresist resin paste containing 30% PGMEA.
[0053] The film retention rates in the following examples are obtained by testing using the following method:
[0054] The obtained photoresist resin powder is dissolved in a PGMEA organic solvent to form a photoresist resin glue solution containing 30% PGMEA. The photoresist resin glue solution containing 30% PGMEA is subjected to pre-baking, development and post-baking to measure the film retention rate.
[0055] Example 1
[0056] A strong acid 1200Na cation exchange resin and a strong alkaline 4200Cl anion exchange resin were selected and mixed in a mass ratio of 1:2 between the strong acid cation exchange resin and the strong alkaline anion exchange resin. Subsequently, a Lewis acid (aluminum chloride) accounting for 2% of the total mass of the anion exchange resin and the cation exchange resin was added to the mixture, and the mixed resin was obtained after curing at 120°C for 4 hours.
[0057] 1 kg of the mixed resin prepared above was weighed and filled into a chromatography column with an inner diameter of 100 mm and a length of 1 m to obtain a purification column.
[0058] like Figure 4 As shown, the photoresist resin was added to the purification column at a flow rate of 20 mL / min by a peristaltic pump and mixed for 2 days. The purified photoresist resin system was measured to be neutral. The purified photoresist resin was dried at 80°C for 24 hours to test the photoresist resin before purification ( Figure 1 A in), after purification of photoresist resin ( Figure 1 B) and after the photoresist resin is purified and dried ( Figure 1 C) of the photoresist resin, from Figure 1 It can be seen that no deprotection reaction occurs in the photoresist resin after purification and after purification and drying.
[0059] The removal rate of metal impurities in the purified photoresist resin reaches 99.99%, and the contents of metal impurities Li, Na, Mg, Al, K, Ca, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Pd, Ag, Cd, Sn, Au, and Pb in the obtained photoresist resin are all less than 10 ppb, the total metal impurities are less than 100 ppb, and the moisture content in the photoresist resin is 0.3%.
[0060] After the resin was purified, the photoresist resin solution was neutral, and no deprotection reaction occurred after the resin was dried. After development, the film retention rate was 90.2%.
[0061] Example 2
[0062] A strong acidic 1200Na cation exchange resin and a strong alkaline 4200Cl anion exchange resin were selected and mixed in a mass ratio of 1:2 between the strong acidic cation exchange resin and the strong alkaline anion exchange resin, and then a Lewis acid (aluminum chloride) accounting for 2% of the total mass of the anion exchange resin and the cation exchange resin was added to the mixture, and a mixed resin was obtained after curing at 120°C for 4 hours. 1 kg of the mixed resin prepared above was weighed and filled into a chromatography column with an inner diameter of 100 mm and a length of 1 m to obtain a purification column.
[0063] The purification column was statically flushed with 1 L of anhydrous methanol, and the flushing was repeated 6 times. The water content of the filtrate was measured with a Karl Fischer instrument.
[0064] Table 1 Water content of filtrate of mixed resin after different washing times
[0065] Flushing times Sample weight 1(g) Moisture value1(%) Sample weight 2(g) Moisture content 2 (%) Average moisture content (%) 1 0.00936 61.59 0.00924 61.81 61.70 2 0.00858 19.19 0.00837 20.31 19.75 3 0.00571 6.72 0.00661 6.80 6.76 4 0.00657 3.64 0.00693 3.87 3.76 5 0.22465 1.1 0.21201 1.2 1.2 6 0.21453 0.4 0.21101 0.5 0.4
[0066] Experiments have shown that the more times the washing is done, the more fully the methanol replaces the water in the mixed resin, and the water content of the filtrate will gradually decrease. After washing with anhydrous methanol for 5 times, the water content of the filtrate is 1.2%, which can be used for the purification of photoresist resin. After washing for 6 times, the water content of the filtrate is 0.4%, which is better for the purification of photoresist resin.
[0067] Example 3
[0068] D113 weak acid cation exchange resin and D301 weak base anion exchange resin were selected and mixed in a mass ratio of 1:2, and then Lewis acid (aluminum chloride) accounting for 2% of the total mass of the anion exchange resin and the cation exchange resin was added to the mixture, and a mixed resin was obtained after curing at 120° C. for 4 hours. 1 kg of the prepared mixed resin was weighed and filled into a chromatographic column with an inner diameter of 100 mm and a length of 1 m to obtain a purification column.
[0069] The metal impurities and water in the photoresist resin were treated. After the resin was purified, the photoresist resin solution was neutral, and no deprotection reaction occurred after the resin was dried. After development, the film retention rate was 85.0%.
[0070] Example 4
[0071] The other operations are the same as those in Example 1, except that 1 mol / L sodium chloride solution is added to the photoresist resin.
[0072] Figure 2 A and Figure 2 B in FIG. 1 and B in FIG. 4 are nuclear magnetic resonance characterization images of the purified photoresist resins of Example 1 and Example 4, respectively. Figure 2 It can be seen that even if sodium chloride is added to the photoresist resin system and a large amount of acid is generated in the system, since the feeding ratio of anion exchange resin and cation exchange resin in the mixed resin is appropriate, and since the cation exchange reaction and the anion exchange reaction can occur simultaneously, the hydroxide ions exchanged by the anion exchange resin and the hydrogen ions exchanged by the cation exchange resin will immediately undergo a neutralization reaction, and hydrogen ions or hydroxide ions will not accumulate, thus avoiding the deprotection reaction caused by residual acid. The mixed resin can still effectively remove strong acid, and deprotection will not occur even after high temperature. This shows that the mixed bed resin is universal in treating acids in photoresist resins.
[0073] Comparative Example 1
[0074] The photoresist resin is purified by using the traditional industrial photoresist resin purification process.
[0075] Among them, the NMR characterization of the photoresist resin before purification is as follows Figure 3 As shown in A in FIG, no peak corresponding to the carboxyl group was found, indicating that the photoresist resin system was not acidic (pH=7); the photoresist resin system after purification was acidic, and the pH of the photoresist resin system was measured to be 5.5. By comparison Figure 3 From the nuclear magnetic resonance characterization diagram of the photoresist resin before and after purification, it can be seen that after the photoresist resin is purified ( Figure 3 B), the photoresist resin undergoes a deprotection reaction to produce a peak corresponding to the carboxyl group. The photoresist resin is further dried in an oven at 80°C for 24 hours ( Figure 3 In C), the peak corresponding to the carboxyl group is more obvious, indicating that the acid and high temperature cause the deprotection reaction of the photoresist resin. After the purified photoresist resin containing residual acid is used for preparation and development, the film retention rate is 0%.
[0076] This also shows that the mixed resin of the present application has a good acid removal effect on the photoresist resin.
[0077] The above examples are used to illustrate the specific implementation of the present invention. However, the protection scope of the present invention is not limited to the above exemplary implementation. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for removing residual acid in a photoresist resin, characterized in that: The method comprises: purifying the photoresist resin to be processed by using a mixed resin, wherein the mixed resin is a resin formed by mixing a cation exchange resin and an anion exchange resin.
2. The method according to claim 1, characterized in that The photoresist resin is KrF photoresist resin.
3. The method according to claim 1 or 2, characterized in that: The photoresist resin to be treated contains acid; the total content of acid in the photoresist resin to be treated is not less than 50 mg KOH / g; And / or, the photoresist resin to be treated contains metal impurities; the total content of metal impurities in the photoresist resin to be treated is not less than 10 ppm; And / or, the photoresist resin to be treated contains moisture; the moisture content in the photoresist resin to be treated is not less than 2%.
4. The method according to any one of claims 1 to 3, characterized in that: The cation exchange resin is a strong acid cation exchange resin; And / or, the anion exchange resin is a strong base anion exchange resin.
5. The method according to any one of claims 1 to 4, characterized in that: The mass ratio of the cation exchange resin to the anion exchange resin in the mixed resin is 1:1.5-4.
6. The method according to any one of claims 1 to 5, characterized in that: The mixed resin is prepared by the following method: The mixed resin is prepared by mixing Lewis acid, cation exchange resin and anion exchange resin, and heating and curing.
7. The method according to claim 6, characterized in that The Lewis acid is selected from aluminum chloride and / or ferric chloride; and / or, the mass of the Lewis acid accounts for 1-5wt% of the total mass of the cation exchange resin and the anion exchange resin; And / or, the temperature of the heating and curing is 100 to 150° C.; the time of the heating and curing is 2 to 8 hours.
8. The method according to any one of claims 1 to 7, characterized in that: The method further comprises filtering, that is, filtering the photoresist resin after the mixed resin purification treatment.
9. The method according to any one of claims 1 to 8, characterized in that: The content of total metal impurities in the photoresist resin is less than or equal to 1000 ppb; and the water content in the photoresist resin is less than or equal to 0.5%.
10. The method according to any one of claims 1 to 9, characterized in that: The film retention rate of the photoresist resin solution is not less than 85%.